Key to the non-fossil species of the genus Taeniothrips (Thysanoptera, Thripidae) - Mound, L. A.; Azidah, A. A.; Ng, Y. F. (Zootaxa, 2012)
A table is provided of the 24 non-fossil species currently listed in Taeniothrips. One species, pediculae, is clearly not a member of this genus, dealatus and sexnotatus remain nomina dubia, and angustiglandus is unrecognisable having been based on males only. A key is provided to the remaining 20 species of the genus, including Taeniothrips damansarae sp.n. from Malaysia that has unique setal apices. Many of these 20 species involve recognition problems that are discussed based largely on type material.